2007
DOI: 10.1073/pnas.0704965104
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the receptor guanylyl cyclase GC-D to chemosensory function in the olfactory epithelium

Abstract: The mammalian main olfactory epithelium (MOE) recognizes and transduces olfactory cues through a G protein-coupled, cAMPdependent signaling cascade. Additional chemosensory transduction mechanisms have been suggested but remain controversial. We show that a subset of MOE neurons expressing the orphan receptor guanylyl cyclase GC-D and the cyclic nucleotide-gated channel subunit CNGA3 employ an excitatory cGMP-dependent transduction mechanism for chemodetection. By combining gene targeting of Gucy2d, which enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
267
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(276 citation statements)
references
References 42 publications
9
267
0
Order By: Relevance
“…Experiments used three strains of mice: (1) OMP-GFP ϩ/Ϫ mice, heterozygous for both OMP and GFP (green fluorescent protein) (Potter et al, 2001); (2) Cnga3 Ϫ/Ϫ OMP-GFP ϩ/Ϫ mice in which genetically labeled GGNs were devoid of a functional CNGA3 channel [this strain was obtained by crossing Cnga3 Ϫ/Ϫ mice (Biel et al, 1999;Leinders-Zufall et al, 2007) Calcium imaging and data analysis. We used newborn mice [postnatal day 1 (P1)-P10] to prepare coronal tissue slices (60-to 100-m-thick) of the Grueneberg ganglion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments used three strains of mice: (1) OMP-GFP ϩ/Ϫ mice, heterozygous for both OMP and GFP (green fluorescent protein) (Potter et al, 2001); (2) Cnga3 Ϫ/Ϫ OMP-GFP ϩ/Ϫ mice in which genetically labeled GGNs were devoid of a functional CNGA3 channel [this strain was obtained by crossing Cnga3 Ϫ/Ϫ mice (Biel et al, 1999;Leinders-Zufall et al, 2007) Calcium imaging and data analysis. We used newborn mice [postnatal day 1 (P1)-P10] to prepare coronal tissue slices (60-to 100-m-thick) of the Grueneberg ganglion.…”
Section: Methodsmentioning
confidence: 99%
“…It consists of a cluster of neurons-henceforward referred to as Grueneberg ganglion neurons (GGNs)-that express olfactory marker protein (OMP) and project their axons to a small number of glomeruli in the caudal main olfactory bulb (Fuss et al, 2005;Koos and Fraser, 2005;Fleischer et al, 2006;Roppolo et al, 2006;Storan and Key, 2006). Interestingly, these glomeruli are near the necklace glomeruli innervated by olfactory sensory neurons expressing the receptor guanylyl cyclase GC-D (Fülle et al, 1995;Juilfs et al, 1997;Leinders-Zufall et al, 2007;Walz et al, 2007; for review, see Munger et al, 2009), and both GC-D-expressing neurons and GGNs express elements of a cGMP second messenger pathway, including the cGMP-specific cyclic nucleotide-gated channel CNGA3 and the cGMP-stimulated phosphodiesterase PDE2 (Juilfs et al, 1997;Meyer et al, 2000;Leinders-Zufall et al, 2007;Fleischer et al, 2009;Liu et al, 2009). They differ, however, in the membrane-bound guanylyl cyclases they express; GGNs express guanylyl cyclase type G but not GC-D (Fleischer et al, 2009;Liu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al [21] provided evidence for CO 2 -mediated, carbonic anhydrase type II (CAII)-dependent Ca 2+ signals in GC-D-expressing neurons. By contrast, functional data from both wildtype and gene-targeted mice strongly support a role of GC-D-positive OSNs as sensitive and selective sensors for two natriuretic peptides -uroguanylin and guanylin [31]. Are these findings necessarily contradictory?…”
Section: Subsystem Organization Of the Mammalian Nosementioning
confidence: 49%
“…Uroguanylin was previously shown to induce either GC-independent (in rat principal cells of the cortical collecting duct) or cGMP-dependent (in mammalian olfactory neurons) depolarization (Sindic et al, 2005;Leinders-Zufall et al, 2007). This later study has showed by both patch-clamp and confocal Ca 2+ -imaging studies that uroguanylin evokes an excitatory, cGMP-dependent signaling cascade that increases intracellular Ca 2+ and action potential firing.…”
Section: Discussionmentioning
confidence: 99%